Nutritional status and micronutrient intake (thiamine, pyridoxine, calsium, magnesium) associated with premenstrual syndrome - Siti Muijah; Debby Endayani Safitri (ARGIPA (Arsip Gizi dan Pangan), 2019)
Premenstrual syndrome is one of psychology and physical symptoms in eligible women before menstruation. The causes of premenstrual syndrome are over nutritional status and less micronutrient intake. The purpose of this study was to analyze nutritional status and micronutrient intake (thiamine, pyridoxine, calcium, magnesium) with premenstrual syndrome of female student in senior high school 74 Jakarta. This study used cross sectional method and taking subjects using systematic sampling techniques. This study used semiquantitative food frequency questionnaire and SPAF (Shortened Premenstrual Assessment Form) questionnaire. The results of the chi-square statistic test showed there were relationships between nutritional status, intake of vitamin B1, vitamin B6, and calcium with premenstrual syndrome, but there was no relationship beetween magnesium intake with premenstrual syndrome. Nutritional status and consuming food containing micronutrients, especially of vitamin B1, vitamin B6, and calcium as needed can reduce the risk of premenstrual syndrome.